Pendidikan Kejiwaan Dr.Abdullah Nashih ‘Ulwan: Konsep Dan Implementasinya - Umi Hani (Faculty of Ushuluddin and Humanities, 2018)
Psychological education is the process of educating children from an early age to be brave and frank, not afraid, independent, like to help others, controlling emotions, and adorn themselves with all of self-glory even psychologically and morally in absolute terms. In the concept of psychological education of Dr Abdullah Nashih 'Ulwan in “Tarbiyatul Aulad Fi Al-Islam”, explained there are four factors of the problem in children that must be prevented and treated by educators. The four factors are feeling inferior, fainthearted, unconfidence, and envy. PM Asy-Syifa perform psychiatric development based on the concept of Nashih Ulwan but not directly, but integrated into daily activities and other routines.